Plan estratégico para el desarrollo comunitario del recinto Los Ángeles, cantón Buena Fe, periodo 2015- 2019. - Solórzano Miranda, Adriana Mercedes (2016)
In this research a situational analysis of the enclosure Los Angeles Parish, part of El Canton Buena Fe, in order to develop a strategic plan and design a feasibility study taking into account existing priorities found by the survey of the population of the campus was conducted . The most relevant and necessary to meet the objectives set for proper planning must be carried out in the medium term aspects were reviewed. The design of the feasibility study establishes the references related to the structure that should be undertaken in the medium term for replication on an investment project for the creation of a training center for the community in the activity of creating a microenterprise it allows developed in an additional activity that generates income for their welfare and that of their families and also contribute to economic development of the enclosure, through the creation of jobs. Thus the development of a project in the medium term sustainability promotes creativity with implanted time.